Historical study of the Indonesian education curriculum: A systematic literature review - Laili, Talitha Sahda; Sunarya, Yaya (Universitas Riau Kepulauan, 2024)
Education is an effort to realize human ideals to become an ideal figure. Education is always evolving with the changing times. This research aims to describe the development of the curriculum and its relevance to the goals of Indonesian education based on the background of events in traditional, modern and globalization times. The method used in this research is systematic literature review through data search using the Publish or Perish application. Based on the search results and criteria set, 20 data became the primary source in this research. The results showed that in the traditional era, the goal of Indonesian education led to the formation of moral and virtuous learners based on the teachings of the religion that was developing at that time. Humans were educated in one direction with the lecture method in order to carry out religious values and uphold morality. However, during the colonial period, education in Indonesia was dehumanized because education was directed to fill the needs of the colonial nation. In the modern era or after the colonial period, the purpose of education experienced humanization because the purpose of education was based on the UUD 1945, namely to educate the nation's life. The government began to compile and develop a curriculum as a national education system. In the era of globalization, the education system is aligned with the challenges of 21st century education. The education system leads to improving the ability of students to learn, digital literacy, and have a career in the future.